Adolescent autistic girls navigating their diagnosis in Swedish secondary school - Josefsson, Helena; Taneja Johansson, Shruti (Frontiers in Education, 2024)
IntroductionAdolescent autistic girls in mainstream schools experience more loneliness and exclusion than their peers. Swedish schools have a long tradition of working towards inclusion but, despite this commitment, these girls are at higher risk of absenteeism and failing to achieve educational objectives. Bearing this in mind, it is important to understand how autistic girls navigate their everyday school life from a first-hand perspective and develop a broader understanding of what shapes their opportunities for and barriers to participation.MethodsThis qualitative study draws on multiple semi-structured interviews with 11 autistic girls, aged 13–15, exploring how they navigate having an autism diagnosis within a Swedish secondary school context.ResultsWhile on a personal level the diagnosis itself was mostly perceived as positive, the girls expressed ambivalence about making sense of it in the school context. The girls expressed awareness of the perceptions and understanding of autism in their school setting, and their consequences in terms of both support and exclusion and stigmatisation. The sense of being perceived by others as different, accompanied by a desire to belong and an awareness of stigma, seemed to have a strong impact on how they navigated everyday school life. This created field of tension between the social context of school, its values and norms, and the girls’ personal experiences and views about autism.DiscussionThe girls’ accounts illustrate the complex reality of their school lives post diagnosis. Valuable implications for practice include the need to work towards a discourse in schools in which differences are seen as natural, and guidance post diagnosis to build the girls’ awareness and understanding and enable them to develop strategies for successfully navigating school.